Back to my roots : Living in Zion (United Kingdom : Exodus Films)
Ras Kawintseb left the west twelve years ago to live in Ethiopia. Ever since he arrived to Ethiopia he has been walking barefoot he now lives in Shashemene as a farmer and music teacher. When thousands of Africans are trying to go to the west why did this Rastaman decide to do just the opposite? He has a great story to tell!
Keywords: Rastafarism